I can help - Wilhelm, Hans, 1945- (New York : Scholastic Inc., 2006)
Puppy wants to help. But he only makes a mess. Will he give up?
"Cartwheel books."
Includes Fluency fun words on p. [3] of cover.
Keywords: Dogs -- Juvenile fiction; Helpfulness -- Fiction; Readers (Primary)